2014
DOI: 10.1007/978-94-017-9211-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Mutant p53 Stabilization in Cancer

Abstract: p53 transactivates cell cycle inhibitory, apoptosis or senescence-related genes in response to DNA damage to protect the genetic integrity of the cell. Highlighting its critical tumor suppressor functions, p53 is mutated, lost, or functionally inactivated in nearly all cancers. When mutated within its core DNA binding domain, p53's normal instability is abrogated, and oncogenic gain-of-function properties are observed accompanied by massive accumulation of steady state mutant p53 protein levels relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…These results suggest that mdm2 expression is not a significant determinant of p53 accumulation in mutant OCCs regardless of TP53 mutation status. Mdm2 is an ubiquitin ligase that targets p53 for degradation [33]. Mdm2-catalyzed ubiquitination of mutant p53 is inefficient compared to wild-type p53 ubiquitination, and ubiquitination of mutant p53 is generally low in cancer cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that mdm2 expression is not a significant determinant of p53 accumulation in mutant OCCs regardless of TP53 mutation status. Mdm2 is an ubiquitin ligase that targets p53 for degradation [33]. Mdm2-catalyzed ubiquitination of mutant p53 is inefficient compared to wild-type p53 ubiquitination, and ubiquitination of mutant p53 is generally low in cancer cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of TP53, which are considered to be able to bear ubiquitination, are thought to be involved in the pathogenesis of as many as 60% of colon cancers [24][25][26]. With a prolonged half-life, TP53 protein detected by immunohistochemistry assay has been widely used as a detection method for TP53 mutation [27][28][29]. Although it has been suggested that TP53 plays a critical role in cancer progression [30,31], to our knowledge no published data on the correlation between mutants TP53 and CUL4A, especially the prognostic value of their combined expression pattern exist so far.…”
Section: Introductionmentioning
confidence: 99%
“…As known, there is different p53 status in various type of cancer. It had been reported the cellular mutant p53 exerted oncogenic gain-of-function (GOF) properties, but the mechanisms mediating these functions remain poorly defined [24, 25]. E1A regulates a multitude of cellular proteins.…”
Section: Discussionmentioning
confidence: 99%